Teledentistry and Forensic Odontology: Qualitative Study on the Capacity of Implementation - Sabourin, Céline; Giraudeau, Nicolas; Baccino, Eric; Camarasa, Frédéric; Martrille, Laurent; Inquimbert, Camille (International journal of environmental research and public health, 2023)
The postmortem identification of people without an identity is performed either by using DNA, dental charts, or fingerprints (until advanced decomposition prevents their study). The lack of forensic dentists who can conduct identifications lead us to reflect on the use of digital technology in this area. The aim of this study was to validate the organizational capacity of using teledentistry for the identification of bodies in a forensic medicine department. A mixed observational study was conducted on 55 cases between July 2020 and February 2021 in the Forensic Medicine and Thanatology Department of Montpellier University Hospital. The protocol was structured in five steps: an initial interview with the agent (a forensic autopsy technician/caregiver specialized in forensic medicine), regarding the idea they had in terms of using telemedicine in their daily practice; agent training in the telemedicine system; realization of a clinical examination using an intra-oral camera by the agent; data analysis by a dental surgeon; final interview with the agent. The study was conducted on 55 subjects. The average age was 54 years old, with more than two-thirds of the patients being male (69%). The videos had an average duration of 29 min. There was an increase in visit duration when rigidity was high; this was also the case when there were many dental specificities in the oral cavity. The quality of the videos was either good or excellent. This study showed that remote identification could be considered as a new non-invasive identification tool. Many features were analyzed to create a training guide for forensic institutes.